Cost-effectiveness analysis of spontaneous vaginal delivery vs elective cesarean delivery for maternal outcomes in ColombiaAJOG Global Reports at a Glance - Andrés Sarmiento, MD; Nathalia Ayala, MD, MSc; Kristian K. Rojas, MSc; Mónica Pinilla-Roncancio, MSc, PhD; Nicolás Rodriguez, MD, MSc; Darío Londoño, MD, MSc; Jennifer S. Gil, MD; Andrea Zapata-Arango, MD; Natalia Martinez, MD; José D. Ruiz-Rios, MD (Elsevier, 2023)
BACKGROUND: In worldwide literature, it has been found that cesarean deliveries represent higher costs and are associated with maternal morbidity and other complications. OBJECTIVE: This study aimed to estimate the cost-effectiveness of elective cesarean delivery compared with spontaneous vaginal delivery in short-term maternal outcomes for low-risk obstetrical population in Colombia. STUDY DESIGN: A cost-effectiveness study using a healthcare-system perspective was performed in 2019 in Colombia. The reference population were women with full-term and low-risk pregnancy, either by spontaneous vaginal delivery or elective cesarean delivery under medical or nonmedical indications. An analytical decision model (decision tree) was designed for maternal outcomes. The time horizon was 42 days postpartum, and the health effects were measured by Quality Adjusted Life Years. A review of the literature and a validation process by a national expert committee were conducted to determine the maternal outcomes and estimate their probabilities. Costs were estimated with a top-down analysis, an incremental cost-effectiveness ratio was calculated, and finally, a sensitivity analysis was performed. RESULTS: Within a 42-day time horizon, it was found that spontaneous vaginal delivery is the less-expensive and more-effective mode of delivery, it showed a reduction in costs (324 USD) and a gain in Quality Adjusted Life Years (0.03) compared with elective cesarean delivery. Our analysis suggests that spontaneous vaginal delivery is the dominant alternative compared with elective cesarean delivery. CONCLUSION: Spontaneous vaginal delivery showed to be the cost-effective mode of delivery for low-risk obstetrical population in Columbia. These results are useful not only for obstetricians but for decision makers, who should encourage nationwide health policies in favor of spontaneous vaginal delivery.